The Development of an Integrated Physics Module with Augmented-Assisted-Qur'an for Measurement Material - Handayani, Fitria; Idrus, Hadiyati; Chandra, Artha Nesa; Agustiyanto, Frans Rizal (Impulse: Journal of Research and Innovation in Physics Education, 2023)
The main problems of current research are the limited measuring tools, handout-based teaching materials and 2D illustrated textbooks that are less varied, and the lack of integration of Al-Qur'an material with technology-based applications. In the educational field, one of the technological advancements is Augmented Reality (AR) which provides a shifting experience from 2D images to 3D. Therefore, technological integration is important to realize a physics module about measurement material and the Al-Qur’an to make students interested in learning by associating the teaching material and the everyday life context.  This R&D applied the 4D model (Define, Design, Development, Dissemination). However, this research is limited to the practical development stage. The researchers used validation sheets from 3 aspects: material and media validation by 3 validators, and interpretation validation by 2 validators. The researchers distributed the practicality sheets to 2 teachers and 28 students The results of data analysis of material validation, media validation and expert interpretation obtained percentages consecutive percentages of 94.5%, 83.3%, and 91.6% with the category of very valid. Meanwhile, the practicality of the module based on the educators and students was 98.6% and 86.4% with the category of very practical.